Business Environment Strategy: Is Sale Through Online System Important? A SWOT Analysis Approach - Widya Prananta; Angga Pandu Wijaya (Universitas Trisakti, 2020)
PT PELNI builds online system ticket sales as a solution to improve its services. The purpose of this study is to analyze the procedure for online ticket sales at PT PELNI and formulate strategies that should be selected companies in the implementation of the system using a SWOT analysis diagram. Purposive sampling conducted to obtain a respondent answer. The sample in this study was 12 employees of PT PELNI Semarang, 16 ticket sales agents, each agent as many as three people. This study employs primary and secondary data to analyze. Methods of data collection using questionnaires. PT PELNI’s strategy was adding branch office and ticket sales agents. Whether also expanded marketing networks and socialization systems online. It would be market segmentation in cooperation with PT POS in purchasing tickets ship online. Also could perform integrated communication between the PT PELNI center, a branch, and sales agents for make improvements of the online system’s way to organize and strengthen the existing network, purchasing tickets through the PT PELNI’s website.